How Populists Use Religion(s). A Comparative Study on Italy and France - Alessio Minicozzi (Partecipazione e Conflitto, 2023)
This article analyses how populist radical right parties use religion in their political discourse as a tool to label their identity and target some specific parts of voters. In particular, it considers the cases of the Lega party in Italy and Rassemblement National in France, treated as most similar cases because of their common ideological features (nativism, authoritarianism and populism). Conducting a software-helped qualitative frame analysis of 117 interviews with party representatives released in 2015-2021, this study provides evidence about how these parties act as 'religious political entrepreneurs' and strategically communicate about religion. The empirical analysis confirms that the two cases align to the diffused Islamophobic stances echoed by the constellation of Western populist radical right parties as well as the interaction with the apparently controversial concept of Christian Secularism (Brubaker 2017).